Modal sosial dan kemiskinan di Jawa Barat - Bayu Kharisma; Sutyastie Soemitro Remi; Adhitya Wardhana; Deni Minarso (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This article aims to analyze the effects of social capital on poverty in West Java Province. The data is generated from the results of the 2014 National Socioeconomic Survey (SUSENAS – Survei Sosial Ekonomi Nasional). The measures of social capital are mutual trust, tolerance, group, and networks. This study uses two instrument variables, namely length of residence and residence location to mitigate the endogeneity problem by using the Instrumental Variable Probit (IVP) estimation model. The results show that social capital negatively and significantly affects poverty. Furthermore, length of education as a proxy of human capital also significantly reduces the likelihood that a household becomes poor. Based on the findings, it is crucial that besides improving the infrastructure quality and providing financial assistance for education, governmental agencies in West Java Province facilitate poor households to participate socially and encourage the development of social organizations for the development of social capital as efforts to alleviate poverty in West Java Province.